Potential Of Halal Sport Tourism on Java Island - Dzikrayah, Fithri; Susilawati, Cucu; Hidayat, Agi Attaubah (Likuid Jurnal Ekonomi Industri Halal, 2025)
Halal sports tourism is a sports tourism activity that is equipped with halal facilities. The concept of sport tourism and halal tourism has been widely developed in Indonesia. However, the idea of halal sports tourism still needs to be discovered. According to Databox, Java Island is the most popular island and a favorite tourist destination in Indonesia. Java Island has a variety of natural tourist destinations that are suitable as sports tourism destinations. Apart from that, the majority of the population of Java Island is Muslim. Therefore, this research aims to determine the potential for developing halal sport tourism on the island of Java. This research is qualitative research with descriptive methods. Data collection techniques were carried out through observation, interviews, documentation studies, and literature studies. This research shows that Java Island has great potential for developing halal sports tourism. Sports tourism destinations on the island of Java are divided into halal sports tourism destinations in West Java, Central Java, and East Java. Each province has a halal sports tourism destination consisting of natural, cultural, and artificial destinations. Apart from that, various sports tourism destinations on the island of Java have Muslim-friendly facilities. Thus, halal sports tourism can be developed on Java Island.